My fate according to the butterfly - Villanueva, Gail D. (Scholastic Press, an imprint of Scholastic Inc., 2019)
In one week Sabrina will be eleven-years-old and she would really like to get her estranged parents and her older sister Nadine together for the celebration, especially since the black butterfly landing on her locket has convinced her that she is going to die; Sabrina and her friend Pepper come up with a bucket list, and enlist Nadine's help--but aspiring reporter Nadine is working on a story about the Philippines' war on drugs, and she has uncovered something that may endanger them all, and prove the butterfly is indeed a harbinger of death in Manila.--